Evaluation of Level of Anxiety among the Patients of Hip Osteoarthritis - Ali, Dr. Aadil Ameer (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2022)
Objective: The objective of this study was to evaluate the level of anxiety among patients with hip osteoarthritis (HOA). Materials and Methods: A cross-sectional survey was conducted in multiple hospitals of Sindh and Balochistan provinces of Pakistan from June to October 2020. A self-developed questionnaire was distributed among 98 patients, who were already diagnosed with HOA. The questions mainly consisted of demographic and disease-related questions. The Statistical Package for the Social Sciences version 23 was used to interpret the data acquired from the questionnaires. Results: The majority (n = 56, 57.1%) of the respondents were female, (n = 41, 41.8%) aged 65 and above years. A substantial number of respondents (n = 67, 68.3%) were permanent residents of rural area. After examining the level of anxiety, we found that majority of the participants (n = 44, 44.8%) were moderately anxious followed by (n = 25, 25.5%) severely anxious due to the HOA. Conclusion: The study determined that the patients suffering from HOA were understood to have moderately anxious due to the disease (HOA). To further elaborate on this, patients become slightly physically disable in the later stages due to this disease which leads to anxiety and depression.